Legal Evolution: Analyzing Minerba Law No. 3/2020 Amendments on Reclamation and Post-Mining Responsibilities: Evolusi Hukum: Menganalisis UU Minerba No. 3/2020 Perubahan atas Reklamasi dan Tanggung Jawab Pascatambang - Lestari, Melati Indah; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2024)
This study analyzes shifting norms in Indonesian mining law, focusing on the phrases "and/or" in Article 96 and "guaranteed" in Article 169A paragraph (1) of Law no. 3 of 2020 Minerba. Using a normative method with a statutory approach and historical interpretation, it finds that "and/or" offers flexibility for mining companies in choosing reclamation or post-mining activities, while "guaranteed" is replaced with "can be given," implying stricter conditions for operating permit extensions. This research underscores a redefined responsibility framework, emphasizing adaptability and stringent criteria in mining operations. Highlights : Flexibility in Activity Choice: "And/or" offers mining companies the flexibility to choose between reclamation and post-mining activities, enhancing efficiency. Stricter Permit Conditions: "Guaranteed" replaced with "can be given" implies stricter terms for operating permit extensions, ensuring compliance. Redefined Responsibility Framework: The study reveals a redefined framework emphasizing adaptability and stringent criteria in Indonesian mining law. Keywords: Indonesian mining law, shifting norms, responsibility, reclamation, operating permits